Leech Therapy and Ayurvedic Management in Treating Acne Vulgaris - Farheen Ahmad; C.R. Yadav; Sarika Yadav; Sangeeta Swavat; Pallavi Yadav (AYUSHDHARA, 2025)
Ayurveda, an ancient system of medicine, offers holistic and long-lasting therapeutic approaches with minimal side effects. Acne vulgaris (Mukhadushika) is a common dermatological concern affecting self-esteem and social interactions. This case study highlights the efficacy of leech therapy (Jaloukaavcharan) as a bloodletting (Raktamokshana) procedure in conjunction with Ayurvedic internal medications (Shamana Chikitsa), demonstrating a unique combination approach for acne management. Case Presentation: A 22 years old female patient presented with multiple inflammatory papules and pustules on the face, along with erythema and oily skin, consistent with Acne vulgaris. The primary concerns included persistent facial acne resistant to conventional treatments. Interventions and Outcomes: The treatment approach included bloodletting through leech therapy and Ayurvedic internal medicines for pacification (Shamana Chikitsa). The combined therapy resulted in a significant reduction in acne lesions, improvement in skin texture, and relief from associated symptoms without any adverse effects. Conclusion: This case report supports the potential of integrating bloodletting therapy with Ayurvedic interventions for treating acne. The promising results suggest that Ayurvedic therapies, particularly leech therapy, can offer a safe and effective adjuvant in dermatological care, warranting further clinical studies.